Perancangan Buku Ilustrasi Pengenalan Nama-Nama Pekerjaan Dengan Sistem Isyarat Bahasa Indonesia (SIBI) Untuk Anak-Anak TKLB-B Karya Mulia Surabaya - Fidiyanti, Juke Andiya; Riyanto, Darwin Yuwono; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The purpose of this illustration book design is to make it easier for deaf children learn to know the names of professions. Research conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept of the design of book illustration. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data and conclusions. From the analysis of the data found some keywords which refer to illustration design strategies that will be used to reach the target audiance who ditujuh. After analysis of the data, the concept of virtue or keyword design book illustrations of